The Post-Rana Plaza Regime : Multi-level labour regulation in Bangladesh’s RMG sector - Alam, Mahbubul; Singh, Parbudyal; Pike, Kelly (Relations industrielles / Industrial Relations, 2021)
AbstractIn the wake of the Rana Plaza tragedy, the Accord and the Alliance were launched as two separate private initiatives alongside the National Initiative (NI) to improve the workplace safety of ready-made garment (RMG) workers in Bangladesh. Together, these three initiatives created multi-level labour regulation with both vertical and horizontal layering. From a multi-level governance perspective, we conducted qualitative research by means of interviews (N = 41) and archival data to analyze the post- Rana Plaza labour regulation experience of Bangladesh’s RMG sector. While our findings indicate the effectiveness of the vertical flow of institutional regulation, they also reveal significant horizontal challenges during implementation of the private initiatives alongside the public NI. Participants believed that the Accord and the Alliance were more effective than individual corporation-led private monitoring because they both approached intervention with a focus on select safety issues with time-bound deliverables, expertise and resources and with effective exercise of sanctions for noncompliance. In contrast, most of the participants saw the NI as much less effective, deploring its insufficient resources, lack of transparency in reporting progress and “softness” in punishing noncompliance. Horizontal operations of the Accord and the Alliance along with those of the NI created some complexities, such as differences in remediation recommendations, an oppositional attitude among non-public and public regulatory team members and a burden of remediation costs on factory owners. In the absence of a legal basis for international labour regulation, these findings will help provide a nuanced understanding of the power dynamics involved in negotiating the revised form and extent of international regulation after the expiration of the Accord and the Alliance, thus shedding light on the ever-evolving forms of international labour regulation. This research will contribute to debate among policy makers and scholars on how best to improve workers’ safety in globally dispersed production networks.SummaryFollowing the Rana Plaza tragedy, two private institutional regulation initiatives, the Accord and Alliance, emerged to address ready-made garment workers’ safety in Bangladesh, alongside the public National Initiative. These three initiatives constitute multi-level regulation with vertical and horizontal layering. Employing this governance framework, this qualitative study analyzes these initiatives using interviews (N=41) and archival data. Our findings suggest an effective vertical flow of private institutional regulation but reveal significant horizontal challenges. We also examine the power dynamics during implementation and in negotiating international regulation after the expiration of the Accord and Alliance, in the absence of a legal basis for international labour regulation. This research contributes to the debate among policy makers and scholars over how to improve workers’ safety in globally dispersed production networks.